True versus forged in the cultural heritage materials: the role of PXRF analysis. (17th April 2013) - Galli, A.; Bonizzoni, L.
<x xml:space="preserve">Abstract</x> Forensic and cultural heritage scientific analyses have several similarities. Indeed, they both deal with unique, 'precious' and often quantitatively very limited objects, which have to be preserved as much as possible. Whenever analytical examination is needed, similar requirements have to be met. Furthermore, also in cultural heritage, field scientists are looking for answers about the story behind the artefact, trying to help discovering its provenance, proving its authenticity or supporting a conscious restoration (a wrong knowledge about ancient material caused destructive conservation intervention even in recent times). Energy dispersive X‐ray fluorescence analysis is thus one of the best approaches mainly for the possibility to perform both qualitative and quantitative analyses without losing sample. Moreover, last generation handheld spectrometers allow to perform analytical investigation almost anywhere. In the present paper, after a brief excursus about the possibility of getting answers through energy dispersive X‐ray fluorescence analysis for the most common archaeometric materials, we present a few peculiar case studies in which scientific examination proved to be helpful in solving historical and archaeological uncertainty. Copyright © 2013 John Wiley & Sons, Ltd.